Analyse synchronique et diachronique du mot barbare dans les discours dictionnairiques - Nadia Soussi Ikhlef (Multilinguales)
The present study deals with the evolution of the meaning of the word barbarian (“barbare”) through its diachronic treatment in the definitions of some recognized dictionaries of the French language. The objective of this semantic analysis, through time, is to question the roleof the discourses of certain dictionaries in the social adjustment the word’s meaning. To propose an answer, we have opted for the word “barbarian” which is very loaded at the socio-historical level and much invested at the level of its countless readings, in order to understand the dynamics of its discursive practices of meaning production, those of its new semantic loads, those of its stereotyping and those of its sustainability. This contribution tries to demonstrate that for the understanding of such a process, the word “barbarian” is an appropriate example.